FDA Approval Summary: Atezolizumab or Pembrolizumab for the Treatment of Patients with Advanced Urothelial Carcinoma Ineligible for Cisplatin‐Containing Chemotherapy - Suzman, Daniel L.; Agrawal, Sundeep; Ning, Yang‐min; Maher, V. Ellen; Fernandes, Laura L.; Karuri, Stella; Tang, Shenghui; Sridhara, Rajeshwari; Schroeder, Jason; Goldberg, Kirsten B.; Ibrahim, Amna; McKee, Amy E.; et al. (The oncologist (Dayton, Ohio), 2019)
The U.S. Food and Drug Administration (FDA) granted accelerated approval to atezolizumab and pembrolizumab in April and May 2017, respectively, for the treatment of patients with locally advanced or metastatic urothelial carcinoma who are not eligible for cisplatin‐containing chemotherapy. These approvals were based on efficacy and safety data demonstrated in the two single‐arm trials, IMvigor210 (atezolizumab) and KEYNOTE‐052 (pembrolizumab). The primary endpoint, confirmed objective response rate, was 23.5% (95% confidence interval [CI]: 16.2%–32.2%) in patients receiving atezolizumab and 28.6% (95% CI: 24.1%–33.5%) in patients receiving pembrolizumab. The median duration of response was not reached in either study and responses were seen regardless of PD‐L1 status. The safety profiles of both drugs were generally consistent with approved agents targeting PD‐1/PD‐L1. Two ongoing trials (IMvigor130 and KEYNOTE‐361) are verifying benefit of these drugs. Based on concerning preliminary reports from these trials, FDA revised the indications for both agents in cisplatin‐ineligible patients. Both drugs are now indicated for patients not eligible for any platinum‐containing chemotherapy or not eligible for cisplatin‐containing chemotherapy and whose tumors/infiltrating immune cells express a high level of PD‐L1. The indications for atezolizumab and pembrolizumab in patients who have received prior platinum‐based therapy have not been changed. This article summarizes the FDA thought process and data supporting the accelerated approval of both agents and the subsequent revision of the indications. Implications for Practice The accelerated approvals of atezolizumab and pembrolizumab for cisplatin‐ineligible patients with advanced urothelial carcinoma represent the first approved therapies for this patient population. These approvals were based on single‐arm trials demonstrating reasonable objective response rates and favorable durations of response with an acceptable toxicity profile compared with available non‐cisplatin‐containing chemotherapy regimens. However, based on concerning preliminary reports from two ongoing phase III trials, the FDA revised the indication for both agents in cisplatin‐ineligible patients. Both are now indicated either for patients not eligible for any platinum‐containing chemotherapy or not eligible for cisplatin‐containing chemotherapy and whose tumors have high expression of PD‐L1. 摘要 美国食品和药品管理局 (FDA) 分别于 2017 年 4 月和 5 月同意加速批准将阿特朱单抗和帕博利珠单抗用于治疗无法接受含顺铂化疗的局部晚期或转移性尿路上皮癌患者。上述批准以在两个单臂试验中显示的有效性和安全性数据为依据:IMvigor210(阿特朱单抗)和 KEYNOTE‐052(帕博利珠单抗)。主要终点指标即确定的客观缓解率，在接受阿特朱单抗治疗的患者中为 23.5% [95% 置信区间 (CI):16.2%–32.2%]，在接受帕博利珠单抗治疗的患者中为 28.6%(95% CI:24.1%–33.5%)。在这两个研究中均未达到缓解的中位持续时间，而且，无论 PD‐L1 状态如何，都可以观察到缓解。这两种药物的安全特性与以 PD‐1/PD‐L1 为靶点的批准药剂基本一致。两个正在进行的试验(IMvigor130 和 KEYNOTE‐361)正在检验这两种药物的益处。根据来自上述试验的相关初步报告，FDA 修改了这两种药剂在无法接受顺铂治疗的患者中的适应证。现在，这两种药物适用于无法接受任何含铂化疗或者无法接受含顺铂化疗且肿瘤/浸润免疫细胞表达高水平 PD‐L1 的患者。阿特朱单抗和帕博利珠单抗在既往曾接受铂类治疗的患者中的适应证没有变化。本文概述了支持加速批准这两种药剂以及随后对适应证进行修改的 FDA 思考过程和数据。 实践意义:加速批准阿特朱单抗和帕博利珠单抗用于治疗无法接受顺铂治疗的晚期尿路上皮癌患者，这提出了针对此类患者群体的首个批准疗法。上述批准以单臂试验为依据，与可用的不含顺铂化疗方案相比，此类单臂试验显示出合理的客观缓解率、良好的反应持续时间以及可接受的毒性特征。不过，根据来自两个正在进行的 III 期试验的相关初步报告，FDA 修改了这两种药剂在无法接受顺铂治疗的患者中的适应证。现在，这两种药剂适用于无法接受任何含铂化疗或者无法接受含顺铂化疗且肿瘤表达高水平 PD‐L1 的患者。 This article summarizes the data supporting FDA approval of atezolizumab and pembrolizumab for the treatment of patients with advanced urothelial carcinoma ineligible for cisplatin‐based chemotherapy and the subsequent revision of the indications for both agents.